Seed longevity differs in Astronium fraxinifolium Schott from two geographic regions in Brazil - Pereira Neto, Leonel Gonsalves; Pereira Sartori, Maria Marcia [UNESP]; Toorop, Peter Ewin; Amaral da Silva, Edvaldo Aparecido [UNESP] (Univ Federal Rural Pernambuco, 2019)
The objective of this work was to evaluate the longevity of Astronium fraxinifolium Schott seeds collected in the states of Goias and Minas Gerais in Brazil and analyse its association with local weather conditions during the vegetative and reproductive phases (temperature, precipitation and altitude) and seed oil content. Longevity was tested in a controlled ageing test at a constant temperature of 45 degrees C and relative humidity (RH) of 60, 65 or 70%, followed by germination. Seed longevity was inferior in seeds collected in the state of Minas Gerais and superior in seeds collected in the state of Goias. There was a significant positive correlation between seed longevity and temperature and a significant negative correlation between seed longevity and altitude. No correlation was found between rainfall and seed longevity. In addition, we found a significant negative correlation between seed longevity and oil content, which was associated with an increase in malondialdehyde (MDA) content. Thus, the influence of the maternal environment during seed production should be considered during seed collection for improved ex situ conservation of A. fraxinifolium seeds.
Keywords: ex situ conservation; rainfall; seed storage; temperature